Energy Monitoring in Wave Power Plant Based on Node-Red and ESP 8266 - Berliana Dzakiyya Rosalin (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2024)
Renewable energy in Indonesia includes solar, water or hydro, bioenergy, wind, geothermal, and ocean waves. The large availability of renewable energy, especially ocean waves, is supported by the geographical conditions of Indonesia, which is the largest archipelagic country. Indonesia has 17,499 islands from Sabang to Merauke, while the area of ​​Indonesia is 7.81 km2 and 3.25 million km2 is ocean. This is related to the world's electricity needs which are estimated to reach 1000 EJ (EJ = 1018J) and will continue to increase every day. Depletion of reserves and greenhouse gas emissions do not allow fossil fuel energy to dominate. Therefore, the Node Red and ESP 8266 Based Wave Power Plant is one of the profitable renewable alternative energies on a commercial scale. The design of this prototype uses a pendulum system. The up and down motion of the pendulum will be converted into a rotary motion by the crankshaft and distributed to the pulley and DC generator. Thus, it can distribute electrical energy that is controlled first by the charger controller before entering the battery. Then the INA 219 sensor will detect the amount of voltage and current generated and distributed to the internet (Node Red) via ESP 8266 so that the tool can be monitored remotely.